Privacy and confidentiality in pragmatic clinical trials. (October 2015) - McGraw, Deven; Greene, Sarah M; Miner, Caroline S; Staman, Karen L; Welch, Mary Jane; Rubel, Alan
With pragmatic clinical trials, an opportunity exists to answer important questions about the relative risks, burdens, and benefits of therapeutic interventions. However, concerns about protecting the privacy of this information are significant and must be balanced with the imperative to learn from the data gathered in routine clinical practice. Traditional privacy protections for research uses of identifiable information rely disproportionately on informed consent or authorizations, based on a presumption that this is necessary to fulfill ethical principles of respect for persons. But frequently, the ideal of informed consent is not realized in its implementation. Moreover, the principle of respect for persons—which encompasses their interests in health information privacy—can be honored through other mechanisms. Data anonymization also plays a role in protecting privacy but is not suitable for all research, particularly pragmatic clinical trials. In this article, we explore both the ethical foundation and regulatory framework intended to protect privacy in pragmatic clinical trials. We then review examples of novel approaches to respecting persons in research that may have the added benefit of honoring patient privacy considerations.